Unnoticed Foreign Body (Metallic Hair Clip) Ingestion in An 18 Month Old Child: A Case Report (Bangladesh Journal of Child Health, 2022)
Accidental foreign body ingestion is common in the pediatric age group particularly between 6 months and 5 years. Most ingested foreign bodies pass easily through the esophagus, into the stomach, and are expelled from the body without complications. However, endoscopic removal will require only 10% - 20% of cases to avoid complications. We present the endoscopic removal of a metallic hair clip in the duodenum of an 18 month old child that was unnoticed initially and diagnosed incidentally.BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 182-185